Low‐Frequency Extensions of the Saturn Kilometric Radiation as a Proxy for Magnetospheric Dynamics. Issue 1 (21st January 2018) - Reed, J. J.; Jackman, C. M.; Lamy, L.; Kurth, W. S.; Whiter, D. K.
Abstract: Saturn Kilometric Radiation (SKR) is an auroral radio emission which can be detected quasi‐continuously by the Cassini spacecraft. It has been shown to respond to magnetotail reconnection and to changes in solar wind conditions and thus offers the potential to be used as a remote proxy for magnetospheric dynamics. This work has developed criteria for the selection of low‐frequency extensions (LFEs), powerful intensifications of the main SKR emission, accompanied by an expansion of the SKR to lower frequencies. Upon examination of data from the Cassini Radio and Plasma Wave Science instrument, we detect 282 LFE events which are further grouped into two categories. Shorter events (<20 h) associated with tail reconnection have a median waiting time of ∼10 h, a median duration of 3.1 h and a strong correlation with the northern and southern SKR phase systems. The 60% of the short LFEs have a reconnection event within the preceding 6 h. Longer events (>20 h), associated with increases in solar wind dynamic pressure, can last multiple planetary rotations, have a median waiting time of ∼20 days, and show no relationship with SKR phase. An analysis of the power emitted during LFEs suggests that tail reconnection is not always observed or detected in situ which may partially explain the low correlation between LFEs and tail reconnection. We conclude that short LFEs are a good proxy for reconnection in the tail. Key Points: Developed criteria for selection of SKR low‐frequency extensions based on analysis of 2006 RPWS data Categorized into short LFEs (<20 h) associated with tail reconnection and long events (>20 h) associated with solar wind dynamics We conclude that short LFEs are a good proxy for reconnection in the tail